Ciencia e investigación agraria 2018
DOI: 10.7764/rcia.v45i1.1818
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of different grapevine (Vitis vinifera L.) cultivars to Diplodia seriata and Diplodia mutila

Abstract: M. Ramírez, L.M. Pérez, and J. Montealegre. 2018. Susceptibility of different grapevine (Vitis vinifera L.) cultivars to Diplodia seriata and Diplodia mutila. Cien. Inv. Agr. XX: 93-98. Canes obtained from one-year-old stems of the grapevine cultivars Cabernet Franc, Malbec, Merlot, Sauvignon Blanc and Syrah (all non-grafted) were used as models to test their susceptibility to Diplodia seriata and Diplodia mutila. The results showed that the mean length of lesions caused by D. mutila was 3.2 times larger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…B. dothidea is a pathogen associated with grapevine decline in Iran [ 47 ], cankers on eucalypts in China [ 48 ] and with the fruit rot of apples in Italy [ 49 ]; while D. mutila was found as causal agent of the trunk diseases of several cultivars of grapevines in Chile [ 36 ], canker and dieback of apple trees in China [ 50 ] and the leaf blight of Magnolia grandiflora L. in China [ 51 ]. Here, we identified B. dothidea and D. mutila as seedborne pathogens able to compromise seed germination as well as causing seedling blight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. dothidea is a pathogen associated with grapevine decline in Iran [ 47 ], cankers on eucalypts in China [ 48 ] and with the fruit rot of apples in Italy [ 49 ]; while D. mutila was found as causal agent of the trunk diseases of several cultivars of grapevines in Chile [ 36 ], canker and dieback of apple trees in China [ 50 ] and the leaf blight of Magnolia grandiflora L. in China [ 51 ]. Here, we identified B. dothidea and D. mutila as seedborne pathogens able to compromise seed germination as well as causing seedling blight.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity tests were carried out by inoculating the stem of P. vulgaris . The seeds of the landrace Dente di Morto were sown in sterile soil and grown in a climatic chamber under a photoperiod of 12 h. After 4 weeks, the plants were inoculated with CREA OF 360.4 and CREA OF 420.36 using the V-shaped cut method, previously described by Ramirez et al [ 36 ]. Briefly, a V-shaped cut was done on the plant stem and a plug of the mycelium was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, wood necrosis was more extensive in canes of Merlot and Pinot Noir than in Chardonnay, Cabernet Sauvignon and Sauvignon Blanc inoculated with N. australe , N. luteum and N. parvum (Billones‐Baaijens et al 2014). Ramírez et al (2018) reported Cabernet Franc, Syrah (Shiraz) and Sauvignon Blanc to have significantly more wood necrosis than Merlot and Malbec following inoculation of canes with D. mutila , although there was no difference among cultivars inoculated with D. seriata .…”
Section: Introductionmentioning
confidence: 99%
“…S. sclerotiorum CREA OF 1113.1 was inoculated on 3-week-old broad bean plants (local variety “Lunga”) by the V-shape method [ 91 ], which consists in cutting the plant stem and applying mycelium plugs of 10-day-old colonies on the wounds. Sterile mycelium was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%